First record of a Regular Echinoid (Echinodermata: Echinoidea) from the Gaiman Formation (Early Miocene), Chubut, Argentina - Allende, Aylén (2021)
The cenozoic fossil record of echinoids from Argentina is dominated by irregular echinoids, while regular echinoids are represented by scarce remains. In this regard, isolated plates, spines AND other fragments are known from the Roca (early Paleocene) and Monte León (early Miocene) formations. More complete specimens are known from the Roca, San Julián (late Oligocene) and El Chacay (early Miocene) formations. In this work, we present the first record of a regular echinoid from the Gaiman Formation (early Miocene). This marine unit is composed of whitish mudstones, fine sandstones and tuffaceous beds. The specimen was found in the lower levels of the exposures at Cerro Prismático locality.